We are La Cocina : recipes in pursuit of the American dream - Zigas, Caleb; Landa, Leticia (Chronicle Books, 2019)
"In a package packed with powerful stories and visual storytelling are 75 recipes from some of the great food entrepreneurs who have graduated from La Cocina, for decent home cooks looking for new recipes, and those who want to support a good cause via a beautiful Bay Area cookbook"--